Feasibility Analysis of Koi Fish Cultivation with the Use of Rice Fields as Cultivation Sites - Yeni Sari Wulandari (Agribusiness Journal, 2023)
Indonesia's biodiversity is very diverse, especially ornamental fish, both seawater and fresh water ornamental fish. Commodities of freshwater ornamental fish cultivated in Indonesia are not only local ornamental fish but imported freshwater ornamental fish such as Koi (Cyrpinus carpio) have also been cultivated in several regions of Indonesia. Kediri is a very potential area, especially in the field of ornamental fish cultivation. The Koi fish cultivation center in Kediri is not inferior to the cultivation in the Blitar area which is already famous for Koi fish cultivation. The traditional pond pattern using rice fields as a place for Koi fish cultivation has proven that with makeshift facilities the people of Pranggang Village are able to help their economy. These advantages make this commodity have business prospects that can be developed through cultivation activities. so it is necessary to do a business feasibility analysis to develop a koi fish farming business in the future. Retrieval of data used in this study is the method of observation, interviews and documentation. while for the analysis using qualitative methods, where the researcher as the key instrument, data collection techniques were carried out by means of triangulation (combined). Qualitative method analysis carried out in this study includes business management, production inputs, production processes, outputs, marketing and business development plans.